Revision and 90-day mortality following hip arthroplasty in patients with inflammatory arthritis and ankylosing spondylitis enrolled in the National Joint Registry for England and Wales. Issue 3 (May 2022) - Miller, Laura L; Prieto-Alhambra, Daniel; Trela-Larsen, Lea; Wilkinson, J Mark; Clark, Emma M; Blom, Ashley W; MacGregor, Alexander J
Aim: To assess revision rates and postoperative mortality in patients undergoing hip arthroplasty (HA) for inflammatory arthritis compared to hip osteoarthritis (OA). Methods: The analysis was conducted among cases of HA that were recorded in the National Joint Registry for England and Wales (NJR) between April 2003 and December 2012 and linked to Office for National Statistics mortality records. Procedures were identified where the indication for surgery was listed as seropositive rheumatoid arthritis (RA), ankylosing spondylitis (AS), other inflammatory arthritis (otherIA), or OA. 5-year revision risk and 90-day postoperative mortality according to indication were compared using Cox regression models adjusted for age, sex, American Society of Anaesthesiologists (ASA) grade, year of operation, implant type, and surgical approach. Results: The cohort included 1457 HA procedures conducted for RA, 615 for AS, 1000 for otherIA, and 183, 108 for OA. When compared with OA, there was no increased revision risk for any form of inflammatory arthritis (adjusted HRs: RA: 0.93 (0.64–1.35); AS: 1.14 (0.73–1.79); otherIA: 1.08 (0.73–1.59)). Postoperative 90-day mortality was increased for RA when compared with OA (adjusted HR: 2.86 (1.68–4.88)), but not for AS (adjusted HR: 1.56 (0.59–4.18)) or otherIA (adjusted HR: 0.64 (0.16–2.55)). Conclusions: The revision risk in HA performed for all types of inflammatory arthritis is similar to that for HA performed for OA. The 3-fold increased risk of 90-day mortality in patients with RA compared with OA highlights the need for active management of associated comorbidities in RA patients during the perioperative period.